Elechi Amadi’s The Great Ponds, An Orchestrated Foray into the Jurisprudence of Traditional Dispute Settlement Mechanism in Pre-Colonial Nigeria - Nyeenenwa, Stephen; Amadiwochi, Justin Ogbonda (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
Elechi Amadi’s The Great Ponds, is a masterpiece of a skillfully crafted war machine artifice. In it, the military traits of the author is showed in the form of a litany of a perfectly organised military tactics demonstrable in ambush, attacking strategy, withdrawal, re-enforcement, abandonment, escape and victory celebration. Nonetheless, working our way through the expository and critical analysis of what we find in same novel convincing strains of an orchestrated foray into the jurisprudence of traditional Nigerian settlement mechanism. Relying on Mother Prof. Marie Pauline Eboh’s (2014) book, The Structure Of Igbo Logic As Shown In Dispute Settlement, we will x-ray the logic and jurisprudence of the methods of dispute settlement therein. We will further explore and critically examine the epochs of conflict and war that engulfed the warring communities, the chequered struggle to control the community’s natural resource – The Wagaba Pond – band to seek to espouse the dangers of war and conflict. We will conclude by drawing on the undeclared aversion of the author to communal conflicts and war, and proceed to assert unabashedly that war and violence ain’t a good option for crisis management. We will recommend that the principle of give and take, of restraint and of nipping brewing troubles in the bud at its earliest stages are invaluable in building a beneficial and cost effective conflict resolution mechanisms and a prelude to building a formidable jurisprudence for our local communities today.